The right to information from the point of view of legal theory, international law and international relations - Федоров, Валентин Андрійович; Федоров, В. А.; Fedorov, Valentyn A.; Федорова, Тетяна Сергіївна; Федорова, Т. С.; Fedorova, Tetiana S.; Дронов, Владислав Юрійович; Дронов, В. Ю.; Dronov, Vladyslav Y. (Florencia : Editorial Primmate S. A. S., 2023)
Taking into account the informatization of public life, the growing role of information, and the development of the information society, the right to information is important not only as a certain set of powers but also as a priority vital interest, the implementation of which has a decisive impact on the life of a modern person. The purpose of the work is the study of information rights in the context of law per se, from the point of view of establishing the researched law at the international level and with regard to international relations regarding information. Research methodology consists of such methods as comparative legal method, inference, hermeneutic method, induction and deduction method, and historical legal method. As a result of the conducted research, it was concluded that the legal regulation of the right of citizens to access public information is one of the most important guarantees of the development of any democratic society. It is concluded that the establishment of the right to information and access to public information at the international level has a positive effect on the realization of fundamental rights by citizens, as well as on the activities of authorities and institutions of public society.
Fedorov V. The right to information from the point of view of legal theory, international law and international relations / V. Fedorov, T. Fedorova, V. Dronov // Amazonia Investiga. – Florencia : Editorial Primmate S. A. S., 2023. – 12(68). - P. 324-332. URL: https://doi.org/10.34069/AI/2023.68.08.30
Keywords: information; right to information; access to information; information with limited access; international standards; international rights